Microfinance in the agenda of the spanish public cooperation for development - Cascante, Rafael (Revista Española de Desarrollo y Cooperación, 2023)
Microfinance has been an important part of the Spanish official cooperation agenda. Starting from this point, the article makes a critical review on the evolution of this topic, pointing out those areas that required further attention, changes aroused in the regulatory framework, as well as some reflections on the future of microfinance cooperation.